2007
DOI: 10.1073/pnas.0609454104
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamic properties of propane coordinated to TpRh(CNR) from a confrontation between theory and experiment

Abstract: density functional theory ͉ hydrocarbon activation ͉ rhodium ͉ selectivity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…They computed an activation energy of ∼6.5 kcal/mol for this process. Clot and Eisenstein located a similar transition state for the 1,2‐migration process of the σ‐alkane complexes of [Tp′Rh(CNMe)] (Tp ′ = HB–(3,5‐dimethylpyrazolyl) 3 ) using DFT and estimated a lower activation barrier for this migration compared with the CH activation and alkane dissociation processes in the same system . These results complement, and are consistent with, the experimental reports of Jones …”
Section: Introductionsupporting
confidence: 85%
“…They computed an activation energy of ∼6.5 kcal/mol for this process. Clot and Eisenstein located a similar transition state for the 1,2‐migration process of the σ‐alkane complexes of [Tp′Rh(CNMe)] (Tp ′ = HB–(3,5‐dimethylpyrazolyl) 3 ) using DFT and estimated a lower activation barrier for this migration compared with the CH activation and alkane dissociation processes in the same system . These results complement, and are consistent with, the experimental reports of Jones …”
Section: Introductionsupporting
confidence: 85%
“…However, these studies only examined a limited number of linear alkanes. Although fast time-resolved studies have not been reported for Tp*Rh­(CNR)­(alkane), activation and reductive elimination for small linear alkane complexes have been studied both experimentally and computationally, where the results parallel those of Tp*Rh­(CO)­(alkane). …”
Section: Introductionmentioning
confidence: 99%
“…examined the related (4,4′‐dibromotolane)platinum(0) diphoshine complex and observed an initial coordination to the central CC bond followed by CBr oxidative addition 11. Weak interactions between saturated hydrocarbons and metal complexes have been observed as well 4e. 12 However, the use of intramolecular reaction channels to selectively functionalize a compound is rare 13.…”
Section: Introductionmentioning
confidence: 99%